Music and basic skills: learning skills (1/2) (Journal of Parents and Teachers, 2012)
This article makes a reflection about the seventh competence which is the competence of learning to learn. The explanation of this competence is divided in two articles. This first one focuses all the attention on activities for children of primary education with two songs.
Keywords: Music; competences; learning; music and education